How Basic Scientists Help the Pharmaceutical Industry Market Drugs - Fugh-Berman, Adriane (Public Library of Science, 2013)
Basic science research is not immune to the influence of pharmaceutical and industrial partners. This Perspective by Adriane Fugh-Bermann explains why scientists should be aware of the potential competing interests posed by practices such as selective publication and ghost-writing.